REGIONAL ASPECTS OF MEDICAL TOURISM DEVELOPMENT IN UZBEKISTAN - Khojimurod Khasanov Tuychiboy ugli; Kenjayeva Mukhlisa (TADQIQOTLAR.UZ, 2024)
Abstract: This article talks about medical tourism, which is a part of tourism that is developing in Uzbekistan, and the territorial aspects of its development, as well as medical centers that receive tourists.